Integrating industrial tourism into active industrial companies: Advantages, barriers, and strategic approaches using the delphi method - Montenegro, Z.; Marques, J.; Sousa, C. (Revista de Gestão Social e Ambiental, 2024)
Objective: This article explores how to incorporate industrial tourism into active industrial companies, whose main focus is industrial production rather than tourism. In contrast to most of the research on industrial tourism, this article focuses on the point of view of active industrial companies, the so-called "living industry", to identify the impact of this product on industrial companies, as well as strategies and barriers to its implementation. Theoretical Framework: Industrial tourism includes visits to industrial sites that have ceased their operations, industrial companies currently in operation and future industrial establishments, as well as visits to other destinations with an industrial theme, such as industrial technology hubs, museums, industrial tourist routes, educational institutions with industrial programs, laboratories and similar sites. Method: The Delphi methodology was employed, involving 27 experts, both academics and practitioners, with different backgrounds, such as Anthropology, Tourism, Business Sciences, Marketing, Economics, International Public Relations, History, Museology, Cultural Heritage, Art and History. Results and Discussion: The results provide new knowledge on the advantages, weaknesses, strategies and barriers to implementing Industrial Tourism in active industrial companies, promoting the development of l business strategies and future studies on this subject. Implications of the Research: The research contributes to understanding the challenges to implementing this tourism product, offering a basis for analyzing and formulating successful business strategies. Originality/Value: The study proposes a practical approach to the applicability of industrial tourism to industrial companies, providing relevant information for industrial companies, government bodies and other stakeholders. ******************************************************************************************************************************************** Objetivo: Este artigo explora como incorporar o turismo industrial em empresas industriais ativas, cujo foco principal é a produção industrial e não o turismo. Em contraste com a maior parte da investigação sobre o turismo industrial, este artigo centra-se no ponto de vista das empresas industriais ativas, a chamada “indústria viva”, para identificar o impacto deste produto nas empresas industriais, bem como estratégias e barreiras à sua implementação. Referencial teórico: O turismo industrial inclui visitas a locais industriais que cessaram as suas operações, empresas industriais atualmente em funcionamento e futuros estabelecimentos industriais, bem como visitas a outros destinos com um tema industrial, como centros de tecnologia industrial, museus, rotas turísticas industriais, instituições de ensino com programas industriais, laboratórios e locais semelhantes. Método: A metodologia de Delphi foi empregue, envolvendo 27 especialistas, tanto académicos como profissionais, com diferentes origens, como Antropologia, Turismo, Ciências Empresariais, Marketing, Economia, Relações Públicas Internacionais, História, Museologia, Herança Cultural, Arte e História. Resultados e conclusões: Os resultados fornecem novos conhecimentos sobre as vantagens, os pontos fracos, as estratégias e as barreiras à implementação do Turismo Industrial em empresas industriais activas, promovendo o desenvolvimento de estratégias empresariais e estudos futuros sobre esta temática. Implicações da pesquisa: A investigação contribui para a compreensão dos desafios da implementação deste produto turístico, oferecendo uma base para a análise e formulação de estratégias empresariais de sucesso. Originalidade/valor: O estudo propõe uma abordagem prática da aplicabilidade do turismo industrial às empresas industriais, fornecendo informações relevantes para as empresas industriais, os organismos governamentais e outros stakeholders. ******************************************************************************************************************************************** Objetivo: Este artículo explora cómo incorporar el turismo industrial a las empresas industriales activas, cuyo foco principal es la producción industrial y no el turismo. A diferencia de la mayoría de las investigaciones sobre turismo industrial, este artículo se centra en el punto de vista de las empresas industriales activas, la denominada «industria viva», para identificar el impacto de este producto en las empresas industriales, así como las estrategias y barreras para su implantación. Quadro teórico: El turismo industrial incluye visitas a emplazamientos industriales que han cesado su actividad, empresas industriales actualmente en funcionamiento y futuros establecimientos industriales, así como visitas a otros destinos con temática industrial, como centros tecnológicos industriales, museos, rutas turísticas industriales, instituciones educativas con programas industriales, laboratorios y emplazamientos similares. Método: Se empleó la metodología Delphi, en la que participaron 27 expertos, tanto académicos como profesionales, con diferentes formaciones, como Antropología, Turismo, Ciencias Empresariales, Marketing, Economía, Relaciones Públicas Internacionales, Historia, Museología, Patrimonio Cultural, Arte e Historia. Resultados y discusión: Los resultados aportan nuevos conocimientos sobre las ventajas, debilidades, estrategias y barreras para la implantación del Turismo Industrial en empresas industriales activas, promoviendo el desarrollo de estrategias empresariales y futuros estudios sobre esta materia. Implicaciones de la Investigación: La investigación contribuye a comprender los retos de la implantación de este producto turístico, ofreciendo una base para analizar y formular estrategias empresariales de éxito. Originalidad/Valor: El estudio propone un enfoque práctico de la aplicabilidad del turismo industrial a las empresas industriales, proporcionando información relevante para las empresas industriales, los organismos gubernamentales y otras partes interesadas